Pertambahan Berat Badan Harian dan Peningkatan Nilai Jual Sapi Bali yang Diberikan Molasses Multinutrient Soft Level 5% dan 10% - Herfandi, Herfandi; Syarifuddin, Syarifuddin; Muchlis, Ahmad (Program Studi Peternakan Fakultas Pertanian Universitas Bosowa, 2023)
This research aims to determine the effect of 5% and 10% MMS supplementation on daily weight gain and the increase in the selling value of Bali cattle. The study involved 12 Bali cattle aged 1-4 years, with body weights ranging from 100-300 kilograms. Basal feed was provided ad libitum, while MMS supplementation was given according to the treatment presentation in the MMS nutrient feed. Based on the results and discussion of this study, it can be concluded that the addition of 5% and 10% MMS supplementation significantly increased the daily weight gain and selling value of Bali cattle compared to the control group (P0) and the other treatment group (P2). Further research is recommended to explore the effects of different levels of MMS supplementation while also considering the uniformity of age and gender among the Bali cattle in the study.